No sex difference was found in the safety and efficacy of intravenous alteplase before endovascular therapy - Fang, Min; Xu, Chenhaoyi; Ma, Lan; Sun, Yue; Zhou, Xiaoyu; Deng, Jiangshan; Liu, Xueyuan (Frontiers in Neurology, 2022)
Background and purpose Prior studies on sex disparities were post-hoc analyses, had limited treatment modalities, and had controversial findings. Our study aimed to examine whether sex difference modifies the effect of intravenous alteplase before endovascular therapy. Methods We conducted a multicenter prospective cohort study of 850 eligible patients with acute ischemic stroke who underwent endovascular therapy. A propensity score was utilized as a covariate to achieve approximate randomization of alteplase pretreatment. The baseline characteristics of women and men were compared. Logistic regression with interaction terms, adjusted for potential confounders, was used to investigate the effect of sex on the prognosis of bridging therapy. Results In comparison to men, women were older [78.00 (70.00–84.00) vs. 67 (61.00–74.00), P < 0.001], had more atrial fibrillation (61.4 vs. 35.2%, P < 0.001), had a lower ASPECTS [10.00 (8.00–10.00) vs. 10 (9.00–10.00), P = 0.0047], and had a higher NIHSS score [17.00 (14.00–20.00) vs. 16 (13.00–19.00), P = 0.005]. Women tended to receive less bridging therapy (26.3 vs. 33%, P = 0.043) and more retrieval attempts [2.00 (1.00–2.00) vs. 1 (1.00–2.00), P = 0.026]. There was no sex difference in functional independence at 90 days after bridging therapy (OR 0.968, 95% CI 0.575–1.63), whereas men benefited more after EVT alone (OR 0.654, 95% CI 0.456–0.937). There were no sex-treatment interactions observed regardless of the location of the occlusion. There were no significant sex differences in all safety outcomes. Conclusion Our study could not confirm that sex modifies the treatment effect of intravenous alteplase before endovascular therapy. At the same time, we advocate for women to seek timely medical treatment.